Pacing strategy of a wheelchair athlete in a 5x and 10x Ironman ultra triathlon: a case study - Sousa, C. V.; Nikolaidis, P. T.; Santos Andrade, M.; Vancini, R. L.; Barbosa de Lira, C. A.; Gomes Puccinelli, P. J.; Knechtle, B. (Disability and Rehabilitation: Assistive Technology, 2020)
Objective: For disabled athletes such as wheelchair athletes, there is no knowledge about competing and pacing during a long-distance triathlon such as an Ironman triathlon. This study aimed to investigate the pacing strategy of a paraplegic wheelchair athlete competing and finishing a Quintuple Iron ultra-triathlon (i.e., five times 3.8 km swimming, 180 km handbike cycling and 42.195 km wheelchair racing in five days) and a Deca Iron ultra-triathlon (10 times the same distance in 10 days). Methods: Data from an ultra-distance triathlon race (Swissultra) covering 5x and 10x Ironman distance were collected. Official performance data were acquired from the race organizer`s website and athlete`s personal information from the athlete through online interviews. The athlete is a man born in 1962, the races analysed in this study were held in the summer of 2017 (5x) and 2019 (10x). The split times for swimming, cycling and running, the overall race times for each Ironman and the lap times in cycling (handbike) and running (wheelchair) were analysed. Results: The athlete finished the Quintuple Iron ultra-triathlon in an overall race time of 66:28:31 h:min:s and the Deca Iron ultra-triathlon in 137:03:20 h:min:s. He adopted an even pacing in both races in split disciplines and for overall race time. Conclusion: The paraplegic wheelchair athlete was able to finish both a Quintuple and a Deca Iron ultra-triathlon by adopting an even pacing in all split disciplines and for overall race time.